DISPLACEMENT DISTRIBUTION MODEL OF ANDESITE ROCK MASS DUE TO BLASTING ACTIVITY USING FINITE ELEMENT METHOD - Agus Nugroho; Asep Bahtiar Purnama (Puslitbang tekMIRA, 2015)
In mining operation, blasting is the most common method to disperse rocks. Blasting process does not only minimize rock fraction, but also produce less favourable energy for its surroundings. One of less favourable energies is ground vibration. The ground vibration will affect slope stability, because it will increase the driving force of the slope to collapse. Thereby, a research is needed to understand the influence of ground vibration in the slope stability. From the level of ground vibration influence on slope stability, it can be set the limit of the blasting process to keep the slope stable. Numerical method that used in this research is finite element method. One of its advantages is to accomodate time element in its calculations. Analysis results of this method are the displacements distribution model of the rock mass in static and dynamic conditions. On the track of A-A’, rock mass displacement took place at the crest of 6.6 mm (static condition) to 8.5 mm (dynamic condition). Likewise, the track of B-B’ line of 0.4 mm to 2.5 mm and line C-C’ from 0.6 mm to 2.0 mm. The safety factor value on the floor of the lines B-B ‘and C-C’ in the dynamic conditions is 1.3. This value is quite prone, so it needs a treatment at the mine slope in order not endanger workers’ safety, mining equipment and the surrounding buildings.